Buck-Boost/Forward Hybrid Converter for PV Energy Conversion Applications - Sheng-Yu Tseng; Chien-Chih Chen; Hung-Yuan Wang (International Journal of Photoenergy)
This paper presents a charger and LED lighting (discharger) hybrid system with a PV array as its power source for electronic sign indicator applications. The charger adopts buck-boost converter which is operated in constant current mode to charge lead-acid battery and with the perturb and observe method to extract maximum power of PV arrays. Their control algorithms are implemented by microcontroller. Moreover, forward converter with active clamp circuit is operated in voltage regulation condition to drive LED for electronic sign applications. To simplify the circuit structure of the proposed hybrid converter, switches of two converters are integrated with the switch integration technique. With this approach, the proposed hybrid converter has several merits, which are less component counts, lighter weight, smaller size, and higher conversion efficiency. Finally, a prototype of LED driving system under output voltage of 10 V and output power of 20 W has been implemented to verify its feasibility. It is suitable for the electronic sign indicator applications.